2015
DOI: 10.1007/978-3-662-47672-7_41
|View full text |Cite
|
Sign up to set email alerts
|

Relative Discrepancy Does not Separate Information and Communication Complexity

Abstract: Does the information complexity of a function equal its communication complexity? We examine whether any currently known techniques might be used to show a separation between the two notions. Ganor et al. recently provided such a separation in the distributional case for a specific input distribution. We show that in the non-distributional setting, the relative discrepancy bound is smaller than the information complexity, hence it cannot separate information and communication complexity. In addition, in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, [12] showed several interesting connections between the relative discrepancy method and other lower bounds techniques (see Section 3 for more details).…”
Section: Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, [12] showed several interesting connections between the relative discrepancy method and other lower bounds techniques (see Section 3 for more details).…”
Section: Techniquesmentioning
confidence: 98%
“…In a followup work, [12] showed that the relative discrepancy bound can be described as the optimum value of a maximization program, which is a relaxation of the partition bound defined by [17]. [12] noted that the variant in which ρ in Definition 1 is any function ρ : {0, 1} n × {0, 1} n → R (not necessarily non-negative), such that x,y ρ(x, y) = 1, is equivalent to the partition bound (up to multiplicative factors that depend on the error probability).…”
Section: Connections To Other Lower Bounds Techniquesmentioning
confidence: 98%
See 1 more Smart Citation